Adolescent Girls' Experiences Regarding Teenage Pregnancy in the Rural Villages of Limpopo Province, South Africa - Patrone Rebecca Risenga; Sheillah Hlamalani Mboweni (MDPI AG, 2022)
Every year, 7.3 million girls become pregnant before they turn 18. Teenage pregnancy increases when girls are denied the right to make decisions about their sexual health and well-being, which is a gender equality issue. Among the challenges of gender equality are those expectations that communities have about girls and early motherhood, sexual violence, and rape. Another challenge is the early marriages of children to older men coupled with the unique risks faced by these girls during pregnancy, for example, the interruption of their education, health risks, such as HIV, premature birth, and increased maternal mortality, denying the girls the right to live a healthy life. This study sought to explore the experiences of adolescent girls regarding teenage pregnancy in the rural villages of the Mopani District, Limpopo. A descriptive, explorative, and qualitative design was followed to collect data from 20 pregnant teenagers in a 13-19 years-old age group. A nonprobability purposive sampling method was used to select the participants from the three villages of the Mopani District. The data were collected using an in-depth individual interview. Tesch's eight steps of data analysis were also applied. The study findings reveal several factors that explain the high rates of teenage pregnancy in rural Limpopo. Among these are the socioeconomic and cultural factors that predispose teens to pregnancy. The consequences of teenage pregnancy were expressed in terms of regret and ill health.